2003
DOI: 10.1021/jo034948y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Experiment Reveal an Unexpected Stereoelectronic Effect on Conformation and Scalar Couplings of α-Aminoorganostannanes, with Possible Relevance to the Tin−Lithium Exchange Reaction

Abstract: The solution conformation of N-methyl-2-(tributylstannyl)piperidines has been determined through the use of vicinal 119Sn-13C coupling constants, revealing a conformational distortion caused by an unexpected stereoelectronic effect in some cases. Specifically, the "equatorial" conformer is distorted into a half-chair, in which the nitrogen lone pair eclipses the C-Sn bond. This distortion, which "costs" approximately 1 kcal/mol, correlates with a conformational dependence of geminal 119Sn-15N couplings and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…[12] These experimentally ascertained values appear to be far from the predicted ones when strongly withdrawing groups such as tert-butoxycarbonyl are present on nitrogen. [11] These Karplus-type curves are well established for 3 …”
Section: Nmr Assignment Of the Trans And Cis Diastereomersmentioning
confidence: 88%
See 1 more Smart Citation
“…[12] These experimentally ascertained values appear to be far from the predicted ones when strongly withdrawing groups such as tert-butoxycarbonyl are present on nitrogen. [11] These Karplus-type curves are well established for 3 …”
Section: Nmr Assignment Of the Trans And Cis Diastereomersmentioning
confidence: 88%
“…[6] A general analysis of the potential information provided by vicinal 3 J( 119 Sn,13 C) coupling constants and by parameters that can be modified by anomeric effect was first examined. [11] by its inclusion in the previously reported 3 J( 119 SnϪCϪCϪ 13 C) KitchingϪKarplus curve. [12] These experimentally ascertained values appear to be far from the predicted ones when strongly withdrawing groups such as tert-butoxycarbonyl are present on nitrogen.…”
Section: Nmr Assignment Of the Trans And Cis Diastereomersmentioning
confidence: 91%
“…Compounds 8 and 9 have been recently studied by Santiago et al [23] who reported some additional 3 J( 119 Sn, 13 C) coupling constants, in which, in some cases, the connection is through the nitrogen atom; although the isoquinuclidine skeleton of these molecules is rigid, there is the possibility of a cis/trans isomerism for the carbonyl group in 8 and a syn/anti isomerism for the N-methyl group in 9. In addition, the butyl chains may have several gauche/trans conformations, although the investigated models are always in the alltrans arrangement.…”
Section: J(mentioning
confidence: 99%
“…[22] Some additional examples of "through N" vicinal 119 Sn-13 C coupling constants have been also reported for isoquinuclidine derivatives. [23] Although the above mentioned relationships involving n J( 119 Sn, X) are undoubtedly useful in organotin(IV) structural studies, their use is often confined to specific structural patterns since they arise from empirical approaches. For example, in the case of di-and tri-methyltin(IV) derivatives the well-known 2 J( 119 Sn, 1 H) vs. θ Lockhart-Manders relationship [12] fails for cis-methyl configuration in hexacoordinate dimethyltin(IV) derivatives and it needs to be differently parameterized when heavy atoms, like chlorine or bromine, are bound to tin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, N-methyl-2-(tri-nbutylstannyl)pirimidines have been studied in solution using NMR techniques showing distortion of the equatorial conformer to a half chair in some cases, something that could influence tinlithium transmetalation reactions. 401 5-Stannylated N-Boc-protected 2,3-dihydro-1H-pyrrole 214 has been recently obtained by direct lithiation-stannylation of the corresponding N-Boc-pyrroline, and has been used in a Stille cross-coupling reaction with the vinyl triflate 215 to give the trienecarbarbamate 216. This compound has been heated to effect an electrocyclic ring closure and oxidized in situ with manganese(IV) oxide to give the marine sponge metabolite (±)-cis-trikentrin A (217) after Bocdeprotection and aromatization (Scheme 64).…”
mentioning
confidence: 99%